Abnormal blocking of a guided mode propagating in a silicon optical waveguide with periodic tunnel coupling. (February 2017) - Kolosovskii, E.A.; Tsarev, A.V.
Abstract: This paper considers abnormal blocking of a guided mode propagating in a silicon optical waveguide with periodic tunnelling inserts. Using an independent two-dimensional analysis by the method of lines (MoL) and direct simulation by the finite-difference time-domain (FDTD) method, we have identified additional signal blocking bands, unrelated to Bragg conversion to backward guided modes of the parent silicon waveguide. These bands are due to the conversion of the incident wave energy to a leaky quasi-mode of the periodically segmented structure, which subsequently transfers the energy to the ambient medium in the form of radiation modes. A distinctive feature of this phenomenon is resonant coupling of the guided mode of the strip waveguide with its radiation modes, which is due to the weak tunnel coupling with the periodically segmented structure. This structure does not support independent guided propagation, so the energy stored in it is re-emitted to space. The abnormal blocking effect may find application in optical telecommunications elements and in the fabrication of optical sensors.